Efficacy of mindfulness-based intervention (‘mindfulness-based joyful sleep’) in young and middle-aged individuals with insomnia using a biomarker of inflammatory responses: a prospective protocol of a randomised controlled trial in China - Chen Pan; Xiang Wang; Yunlong Deng; Peihuan Li; Yanhui Liao; Xin Ma; Guo-Ping Yang; Lisha Dai; Qiuping Tang (BMJ Open)
Introduction Insomnia is a prevalent and significant public health concern. Insomnia can lead to increased inflammatory markers associated with chronic diseases such as cardiovascular disease, diabetes and cancer. Studies suggest that mindfulness-based interventions (MBIs) are more easily delivered within the community than cognitive behavioural therapy for insomnia (CBT-I) which was recommended as the preferred non-pharmacological treatment by the American Academy of Sleep Medicine, are effective in insomnia treatment and can reduce inflammatory markers level in older individuals with insomnia. This study aims to compare the effectiveness of an MBI to CBT-I in young and middle-aged individuals with insomnia disorder and explore its effect on nuclear factor kappa B (NF-κB), a transcription factor that controls the expression of genes involved in inflammation.Methods and analysis This report describes a protocol for a randomised controlled trial. Seventy eligible participants will be assigned to mindfulness-based joyful sleep or CBT-I for 2-hour sessions weekly for 8 weeks. The primary outcome is sleep quality assessed by the Pittsburgh Sleep Quality Index, severity of insomnia symptoms assessed by the Insomnia Severity Index and sleep parameters recorded using sleep diary and polysomnography. Secondary outcomes include perceived stress, anxiety and depression. The exploratory outcome is serum level of NF-κB. Outcomes will be evaluated at baseline, the end of the ntervention period and at a 3 month follow-up. Data will be analysed using general linear models, specifically analysis of covariance and analysis of variance will be used.Ethics and dissemination Full ethical approval for this study has been obtained from the Ethics Committee of the Third Xiangya Hospital, Central South University, Changsha, China (2018-S236). If Mindfulness-Based Joyful Sleep is proven effective, its dissemination will help bridge the gap between the unmet need and the demand for insomnia interventions in China.Trial registration number NCT03268629; Pre-results.